Insights into Fischer–Tropsch catalysis: current perspectives, mechanisms, and emerging trends in energy research - Keunecke, Arthur; Dossow, Marcel; Dieterich, Vincent; Spliethoff, Hartmut; Fendt, Sebastian (Frontiers in Energy Research, 2024)
Fischer-Tropsch (FT) synthesis is an important module for the production of clean andsustainable fuels and chemicals, making it a topic of considerable interest in energy research.This mini-review covers the current literature on FT catalysis and offers insights into the primaryproducts, the nuances of the FT reaction, and the product distribution, with particular attentionto the Anderson-Schulz-Flory distribution and known deviations from this fundamental concept.Conventional FT catalysts, particularly Fe and Co-based catalysis systems, are reviewed, highlighting their central role and the influence of water and water-gas shift activity on theircatalytic behavior. Various mechanisms of catalyst deactivation are also investigated, and the highmethanation activity of Co-based catalysts is illustrated. To make this complex field accessible to abroader audience, we explain conjectured reaction mechanisms, namely the carbide mechanismand CO insertion. We discuss the complex formation of a wide range of products, including olefins,kerosenes, branched hydrocarbons, and by-products such as alcohols and oxygenates. Thearticle goes beyond the traditional scope of FT catalysis by addressing topics of current interest,including the direct hydrogenation of CO2 for Power-to-X applications and the use of bifunctionalcatalysts to produce tailored FT products, most notably for the production of sustainable aviationfuel (SAF). This mini-review provides a holistic overview of the evolving landscape of FT catalystsand is aimed at both experienced researchers and those new to the field, while covering currentand emerging trends in this important area of energy research.